Dinâmica e distribuição de nematoides gastrointestinais em pastagem com e sem sombra para ovinos durante o verão - Portugal, Miguel Angel Guillen (2021)
This study aimed to evaluate the migratory dynamics and distribution of infective larvae (L3) of gastrointestinal nematodes in two food systems cultivated with Panicum maximum cv. Aruana for finishing lambs in the summer period. A total area of 4,800 m2 was used, divided into 6 paddocks of 400 m² for each treatment (treatment 1: system without shading and treatment 2: system with shade, which were provided with troughs and drinking fountains, making a total of 12 paddocks and 24 animals. Larval recovery was evaluated in 5 sampling periods (0, 21, 42, 63 and 84 days) in each treatment, in three strata of the pasture (lower, intermediate and upper). The parasitological evaluations were carried out every 21 days for a total period of 93 days. The pasture harvest started ten days after the entry of the animals and the feces collection started 21 days after the pasture harvest. A split-plot scheme was used, repeated in a completely randomized time, with the plots being the treatments (food system in the shade and in the sun), and the periods were the evaluation days, analyzed in the statistical package R es everything. The genera identified were Haemonchus contortus, Trichostrongylus spp., Ostertagia spp., Cooperia spp., and Bunostromun spp., with percentages of 67%, 21%, 14%, 1% and 2% respectively. The genera with the greatest distribution was Haemonchus contortus obtained in the upper 75.5%, intermediate 60.25% and lower 40.50% strata. The highest L3 recoveries occurred at 21 days, in the lower stratum (173.00 L3/Kg/MS) in the shade system (P<0.05), followed by period 42 in the upper stratum (187.00 L3/Kg/MS) in system in the sun (P<0.05). The behavior of gastrointestinal nematode infective larvae showed no difference between treatments, but an effect (p<0.05) was observed between the strata within the larval recovery periods. In the summer season, shade systems can be used as an alternative management after the rains for parasite control, avoiding the consumption of high concentrations of infective L3 larvae.